Effects of Electrical Stimulation in Spastic Muscles After Stroke. Issue 8 (August 2015) - Stein, Cinara; Fritsch, Carolina Gassen; Robinson, Caroline; Sbruzzi, Graciele; Plentz, Rodrigo Della Méa
<x xml:space="preserve">Abstract</x> Background and Purpose— Neuromuscular electric stimulation (NMES) has been used to reduce spasticity and improve range of motion in patients with stroke. However, contradictory results have been reported by clinical trials. A systematic review of randomized clinical trials was conducted to assess the effect of treatment with NMES with or without association to another therapy on spastic muscles after stroke compared with placebo or another intervention. Methods— We searched the following electronic databases (from inception to February 2015): Medline (PubMed), EMBASE, Cochrane Central Register of Controlled Trials and Physiotherapy Evidence Database (PEDro). Two independent reviewers assessed the eligibility of studies based on predefined inclusion criteria (application of electric stimulation on the lower or upper extremities, regardless of NMES dosage, and comparison with a control group which was not exposed to electric stimulation), excluding studies with <3 days of intervention. The primary outcome extracted was spasticity, assessed by the Modified Ashworth Scale, and the secondary outcome extracted was range of motion, assessed by Goniometer. Results— Of the total of 5066 titles, 29 randomized clinical trials were included with 940 subjects. NMES provided reductions in spasticity (−0.30 [95% confidence interval, −0.58 to −0.03], n=14 randomized clinical trials) and increase in range of motion when compared with control group (2.87 [95% confidence interval, 1.18–4.56], n=13 randomized clinical trials) after stroke. Conclusions— NMES combined with other intervention modalities can be considered as a treatment option that provides improvements in spasticity and range of motion in patients after stroke. Clinical Trial Registration Information— URL: http://www.crd.york.ac.uk/PROSPERO. Unique identifier: CRD42014008946.